2012
DOI: 10.2478/v10032-012-0001-6
|View full text |Cite
|
Sign up to set email alerts
|

Alternaria Black Spot of Crucifers: Symptoms, Importance of Disease, and Perspectives of Resistance Breeding

Abstract: Alternaria black spot of cruciferous vegetables, incited by different species of Alternaria, remains an increasing threat to Brassicaceae crops throughout the world, including Poland. Brassica plants are attacked by conidia of A. brassicae (Berk.) Sacc., A. brassicicola (Schw.) Wiltsh., A. raphani Groves & Skolko, and A. alternata (Fr.) Kreissler. The pathogens have a wide spectrum of hosts, such as head cabbage, Chinese cabbage, cauliflower, broccoli, and other crucifers including cultivated and wild grown pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
95
0
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 111 publications
(98 citation statements)
references
References 36 publications
1
95
0
2
Order By: Relevance
“…Our data revealed that AtABCG34 is an important factor required for defense against the necrotrophic fungal pathogens A. brassicicola and B. cinerea and that AtABCG34 functions by secreting camalexin to the surface. A. brassicicola infection results in dark leaf spots on most Brassica species, including economically important oilseed crops (50). Infection by A. brassicicola considerably reduces the quality and quantity of harvested Brassica crops (51), resulting in annual yield losses of 15-70% (51).…”
Section: Discussionmentioning
confidence: 99%
“…Our data revealed that AtABCG34 is an important factor required for defense against the necrotrophic fungal pathogens A. brassicicola and B. cinerea and that AtABCG34 functions by secreting camalexin to the surface. A. brassicicola infection results in dark leaf spots on most Brassica species, including economically important oilseed crops (50). Infection by A. brassicicola considerably reduces the quality and quantity of harvested Brassica crops (51), resulting in annual yield losses of 15-70% (51).…”
Section: Discussionmentioning
confidence: 99%
“…Typical disease signs consist of black lesions on seedlings, leaves, stems, and siliquae resulting in accelerated senescence, premature pod shatter, and shrunken seeds (Mac Kinon et al, 1999; Iacomi-Vasilescu et al, 2004). Seeds infected with the pathogen result in reduced seed germination, photosynthetic potential, seedling vigor and pre- and post-emergence damping-off of seedlings (Nowicki et al, 2012), causing significant reduction in yield quantity and quality.…”
Section: Introductionmentioning
confidence: 99%
“…Alternaria brassicicola is a necrotrophic fungal pathogen that causes black spot disease in many cruciferous vegetables, such as broccoli, cabbage, cauliflower, radish and turnip (Nowicki et al, 2012;Otani et al, 1995). A recent survey reported that vegetable crop losses caused by this fungus might be 20-80 % worldwide (Nowicki et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…A recent survey reported that vegetable crop losses caused by this fungus might be 20-80 % worldwide (Nowicki et al, 2012). In addition to its economic importance, the interaction between this pathogen and several ecotypes or mutants of Arabidopsis thaliana has been used as a model system to investigate functions of fungal virulence factors and plant genes and signals modulating disease progression.…”
Section: Introductionmentioning
confidence: 99%